2018
DOI: 10.1007/s40430-018-1294-2
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable machining: an experimental investigation and optimization of machining Inconel 825 with dry and MQL approach

Abstract: Sustainability is a vital issue for present and future generation, and it aims to obtain overall efficiency in terms of economic, environmental and social aspects. Inconel 825 belongs to the family of nickel-based super alloy and is widely used in the chemical and marine industries. This work attempts to investigate machining performance of Inconel 825 using physical vapor deposition-titanium nitrate inserts, with a focus on sustainable machining. The effect of cutting parameters, viz. cutting speed (v), feed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…Further, observed a significant reduction in cutting force, tool wear and white layer depth in MQL over dry cutting respectively. Tamang et al [32] beneficial results were observed with MQL cutting condition due to good lubrication effect over dry condition while turning of Inconel 825 material. Subsequently, optimum process parameters were determined using a genetic algorithm to solve multi objective problem.…”
Section: Introductionmentioning
confidence: 97%
“…Further, observed a significant reduction in cutting force, tool wear and white layer depth in MQL over dry cutting respectively. Tamang et al [32] beneficial results were observed with MQL cutting condition due to good lubrication effect over dry condition while turning of Inconel 825 material. Subsequently, optimum process parameters were determined using a genetic algorithm to solve multi objective problem.…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, constant consumption can be the energy which is consumed even when no actual metal cutting process is running. Tamang et al [17] are even more specific dividing the energy consumption of MTs in three modes:…”
Section: Energy Assessmentsmentioning
confidence: 99%
“…In this mode, the measurement of active power of each component is done separately. As defined in Tamang et al [17], the constant portion of power is related to components that ensure the functionality of the MT in an event of starting the machining process. In such case, the components active in this mode are: internal light, hydraulic unit, lubrication system for guideways, electric panel fan, spindle cooling system, spindle heat exchanger, CNC drives and servomotors, which remain electrically powered, even if none cutting load is applied.…”
Section: Test 1-mode Mt Onmentioning
confidence: 99%
See 2 more Smart Citations